1986
DOI: 10.1002/j.1556-6676.1986.tb01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault Programming for College Students

Abstract: The authors discuss workshops designed to promote awareness of sexual assault and to provide education about such assault on college campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Interpretation of these results is problematic for the reasons cited in the preceding study. Briskin and Gary (1986) had college students participate in a workshop that addressed 24 rape myths and facts. These items were presented in "quiz format" to stimulate discussion and to challenge the participants personal beliefs about sexual assault.…”
Section: Mixed-gender Programsmentioning
confidence: 99%
“…Interpretation of these results is problematic for the reasons cited in the preceding study. Briskin and Gary (1986) had college students participate in a workshop that addressed 24 rape myths and facts. These items were presented in "quiz format" to stimulate discussion and to challenge the participants personal beliefs about sexual assault.…”
Section: Mixed-gender Programsmentioning
confidence: 99%
“…As with the all-female interventions, most mixed-sex programs have reported desirable change in rape-supportive attitudes as a result of participation (Briskin & Gary, 1986;Dallager & Rosen, 1993;Fischer, 1986;Fonow, Richardson, & Wemmerus, 1992;Harrison, Downes, & Williams, 1991;Holcomb, Sarvela et al, 1993;Intons-Peterson, Roskos-Ewoldsen, Thomas, Shirley, & Blut, 1989;Johnson & Russ, 1989;Lenihan, Rawlins, Eberly, BucMey, & Masters, 1992;Mann et al, 1988;Nelson & Torgler, 1990). A few exceptions to this pattern, however, are of particular interest and will be discussed within the context of empathy induction techniques below (Borden, Karr, & Caldwell-Colbert, 1988;Ellis, O'Sullivan, & Sowards, 1992;Schaeffer & Nelson, 1993).…”
Section: Programs Targeting Mixed-sex Audiencesmentioning
confidence: 99%
“…First, these evaluations have relied heavily on standard attitudinal assessment immediately following the intervention, as did the all-female interventions. Second, evaluation of several programs Borden, Karr, & Caldwell-Colbert (1988) 45-min lecture on "rape awareness and prevention" addressed topics of "legal terms, biographical descriptions of a 'typical' rapist, rape trauma syndrome, prevention strategies, and available assistance" (p. 134); the program was conducted in a classroom setting and a second class served as a comparison group for evaluation 50 introductory psychology students (25 male, 25 female) received the Attitudes Toward Rape Questionnaire (Feild, 1978) and Rape Empathy Scale (Deitz, Blackwell, Daley, & Bentley, 1982) preceding the program and after a 4-week follow-up; despite the perception of program success among college students and staff, follow-up responses showed no change in rape-related attitudes; no change was also evident in a comparison class ( n = 50, 25 male, 25 female) Briskin & Gary (1986) College students took part in workshops of 5-25 participants in either residential settings, or as part of freshman orientation or a student organization; 24 myths and facts were presented in quiz format to stimulate discussion and encourage students to commit to choosing an answer, thereby examining personal beliefs "in a supportive and informative environment'' (p. 207); in some formats, the presenter(s) read answers and lead group discussion, in others the participants broke into small groups to reach consensus on items; discussion frequently covered safety precautions, resistance strategies, victim responses, acquaintance rape issues, needs and issues for special populations, significant others, and proactive prevention of rape Based on examination of "consumer satisfaction,'' the authors suggested that "the number of requests for programs was indicative of their perceived value . .…”
Section: Programs Targeting Mixed-sex Audiencesmentioning
confidence: 99%
“…ity, the reliance on pretesting, and the subsequent potential for misinterpreting program "success." Specifically, existing evidence suggests that the majority of rape education programs are successful in reducing the level of rape-supportive ideology (Briskin & Gary, 1986;Earle, 1996;Fischer, 1986;Fonow, Richardson, & Wemmerus, 1992;Frazier, Valtinson, & Candell, 1994;Gilbert, Heesacker, & Gannon, 1991;Hanson & Gidycz, 1993;Hamson, Downes, & Williams, 1991;Holcomb, Sarvela, Sondag, & Holcomb, 1993;Intons-Peterson, Roskos-Ewoldsen, Thomas, Shirley, & Blut, 1989;Johnson & Russ, 1989;Lee, 1987;Lenihan, Rawlins, Eberly, Buckley, & Masters, 1992;Linz, Fuson, & Donnerstein, 1990;Lonsway et al, 1998;Malamuth & Check, 1984;Mann, Hecht, & Valentine, 1988;Nelson & Torgler, 1990;Ring & Kilmartin, 1992;Wilson, Linz, Donnerstein, & Stipp, 1992). However, each of these studies has explicitly linked at least some portion of the outcome evaluation with program participation, thereby raising the concern that the "successful" outcomes are the result of demand characteristics rather than ideological change.…”
mentioning
confidence: 99%